My parents were killed in Sobibor, but it feels as if I was there: Imagination in my Interviews - Leydesdorff, Selma (Historein, 2019)
During the Demjanjuk trial in Munich (2009–2011), I had the unexpected privilege to interview the Nebenkläger (co-plaintiffs) who testified in court about Sobibor. They related extremely sad stories about losing fathers, mothers, spouses and close family. In this article, I attempt to analyse their extreme loneliness and I wonder how to interpret their fragmented language of trauma. What kind of knowledge did they commit, and in what way are their stories different from the stories told by survivors?